Basic Knowledge of Army Troops and their Relatives in Rangpur towards Antibiotic - Nazrina, Sayeda; Chowdhury, Dipak Kumar Paul; Maruf, Abdullah Al; Rahman, Wahida (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Inappropriate use of antibiotic may create several problems including emergence of drug resistant microorganisms, the rising costs of health-care services and the development of side effects. Misconceptions regarding antibiotic can lead to misuse of antibiotics. So, consumers’ knowledge towards antibiotic may play a vital role in the success of treatment process. Objectives: To investigate the level of basic knowledge towards antibiotics among troops of Bangladesh Army and their relatives in Rangpur, Bangladesh. Materials and Methods: This cross-sectional study was conducted from January to March 2015 for 12 weeks using the structured questionnaire involving 389 respondents attending outdoor of various departments of Combined Military Hospital (CMH), Rangpur. A random knowledge score system was used to assess basic knowledge based on the answers provided. Results: The mean age of the respondents was 30.434 years (SD=6.5365) with male (53.47%) predominance. Out of 389 respondents, 219(56.30%) respondents had a moderate level of knowledge. Most of the respondents (89.72%) could correctly identify that antibiotics are indicated for the treatment of bacterial infections. However, 348(89.46%) respondents incorrectly thought that antibiotics are also used to treat viral infections. Most of the respondents wrongly believed that antibiotics are indicated to relieve pain (68.69%) and reduce fever (77.38%). About 270(69.41%) respondents were aware of antibiotic resistance phenomena in relation to overuse of antibiotics. Age, sex and educational level were significantly associated with knowledge towards antibiotic. Conclusion: Educational intervention is needed to promote prudent use of antibiotic. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 12-16